Predictive Physiological Anticipation Preceding Seemingly Unpredictable Stimuli: A Meta-Analysis - Mossbridge, Julia; Tressoldi, Patrizio E.; Utts, Jessica (Frontiers in Psychology, 2012)
This meta-analysis of 26 reports published between 1978 and 2010 tests an unusal hypothesis: for stimuli of two or more types that are presented in an order designed to be unpredictable and that produce different post-stimulus physiological activity, the direction of pre-stimulus physiological activity reflects the direction of post-stimulus physiological activity, resulting in an unexplained anticipatory effect. The reports we examined used one of two paradigms: 1) randomly presented arousing vs. neutral stimuli, or 2) guessing tasks with feedback (correct vs. incorrect). Dependent variables included: electrodermal activity, heart rate, blood volume, pupil dilation, electroencephalographic activity (EEG), and blood oxygenation level dependent (BOLD) activity. To avoid including data hand-picked from multiple different analyses, no post-hoc experiments are considered. The results reveal a significant overall effect with a small effect size (random effects: overall [weighted] ES=0.21, 95%CI=0.13-0.29, z=5.3, p<5.7x10-8; fixed effects: overall ES=0.21, 95%CI=0.15-0.27, z=6.9, p<2.7x10-12). Higher quality experiments produce a quantitately larger effect size and a greater level of significance than lower quality studies. The number of contrary unpublished reports that would be necessary to reduce the level of significance to chance (p>0.05) was conservatively calculated to be 87 reports. We explore alternative explanations and examine the potential linkage between this unexplained anticipatory activity and other results demonstrating meaningful pre-stimulus activity preceding behaviourally relevant events. Multiple replications arising from different laboratories using the same methods are necessary to further examine this currently unexplained anticipatory activity. The cause of this anticipatory activity, which undoubtedly lies within the realm of natural physical processes (as opposed to supernatural or paranormal ones), remains to be determined.